STRATEGIC EDGE : HOW MARKET AND COMPETITOR ORIENTATION DRIVE RETAIL PERFORMANCE - Fendy Cuandra; Rio Fernando; Lily Purwianti; Listia Nurjanah (Nurul Jadid University, 2025)
This study aims to evaluate the influence of competitor orientation, market orientation, innovation, marketing strategy, and marketing through social media on marketing performance, with competitive advantage as a mediating variable. A quantitative approach with descriptive methods was used in this study. Primary data were collected from 350 respondents who are employees of retail companies in Batam City and analyzed using SmartPLS 3 software. The results show that most of the independent variables have a positive and significant effect on competitive advantage, which in turn has a strong impact on improving marketing performance. The findings strengthen the understanding that effective implementation of competitor orientation, market orientation, and marketing strategy can enhance competitive advantage as well as marketing performance in the retail industry.